2019
DOI: 10.1021/acs.nanolett.8b03986
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Stability of Carbon Nanotube Transistors Under Long-Term Bias Stress

Abstract: Thousands of reports have demonstrated the exceptional performance of sensors based on carbon nanotube (CNT) transistors, with promises of transformative impact. Yet, the effect of long-term bias stress on individual CNTs, critical for most sensing applications, has remained uncertain. Here, we report bias ranges under which CNT transistors can operate continuously for months or more without degradation. Using a custom characterization system, the impacts of defect formation and charge traps on the stability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…Additionally, this fabrication scheme has been utilized to fabricate CMOS inverters with a pitch size as small as 240 nm. [16] While these advances highlight the potential of SWCNT FETs in aggressively scaled digital technologies, a deeper understanding of how channel length scaling affects other performance metrics (e.g., early device degradation) [121] is needed.…”
Section: Scaling Of Conventional High-performance Swcnt Fetsmentioning
confidence: 99%
“…Additionally, this fabrication scheme has been utilized to fabricate CMOS inverters with a pitch size as small as 240 nm. [16] While these advances highlight the potential of SWCNT FETs in aggressively scaled digital technologies, a deeper understanding of how channel length scaling affects other performance metrics (e.g., early device degradation) [121] is needed.…”
Section: Scaling Of Conventional High-performance Swcnt Fetsmentioning
confidence: 99%
“…Stability and reliability are important concerns to CNT electronics. Few works focused on the stability of CNTFETs [84,85]. CNTFETs, especially the N-type CNTFETs implemented by low work function metal contact, would be sensitive to air, and/or gradually degrade or even fail when exposed to the air without a package.…”
Section: Challenge and Outlookmentioning
confidence: 99%
“…CNTFETs, especially the N-type CNTFETs implemented by low work function metal contact, would be sensitive to air, and/or gradually degrade or even fail when exposed to the air without a package. Although researchers have found that the stability of CNTFETs can be improved through passivation [84,85], some factors, especially including polymer residues in the most mature solution-derived CNTs and interface trapping states, will induce instability during the enduring operation. Additionally, fabricating CNT CMOS FETs with standard industry processes, which are compatible with conventional CMOS processes, is a significant necessity for developing CNT-based integrated circuits.…”
Section: Challenge and Outlookmentioning
confidence: 99%
“…Their fascinating structures have attracted attention of numerous researchers. CNTs are seamless nanoscale tubes made of a single or multilayer graphite coiled at a certain helical angle around a central axis (De Volder et al, 2013 ; Noyce et al, 2019 ). Because of its wide range of thermal, structural, and electronic properties, they have been applied to catalyst and capacitor material support (Gong et al, 2013 ; Yang et al, 2017 ).…”
Section: Application Of Carbon Nanomaterials In Metabolic Disease Detmentioning
confidence: 99%